SPEECH IN VEDIC LITERATURE - Pandey, Krishna Chand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Speech has had a place in the Indian tradition of thought since the beginning. In the oldest Ve-dic literature, Rigveda, we find verses that propound the importance of speech. Along with this, we also find the seeds of thought that connect speech with the mystery of creation. After this, in the later Vedic literature, we find many stories related to speech that refer to the various levels of speech. Along with this, in the later Brahman and Aranyaka literature, the process of analysis of spoken language also seems to have begun; because in these, we find discussions here and there on the division of vowels and consonants, division of voiced consonants into voiced and unvoiced, division of sound and vowels, and division of letters. In fact, the Indian tradition has been a speech-centric tradition since the beginning, so not only has speech been given divinity in it, but it has also been imagined that the ultimate position can be attained through the preci-sion of speech and the practice of speech.